Agents and artificial intelligence : 8th International Conference, ICAART 2016, Rome, Italy, February 24-26, 2016, Revised selected papers /: 8th International Conference, ICAART 2016, Rome, Italy, February 24-26, 2016, Revised selected papers. (2017) - Unknown
No abstract available